SUSTAINABLE DEVELOPMENT AND ExTERNALITIES - Ion, Bucur; Cristian, Bucur (Economics of Agriculture, 2011)
Externalities appear due to the interdependence of production and utility functions of one or more economical agents. Externalities are external effects derived from the behavior of economic agents that changes the wealth of an economic system. Sustainable development requires consideration of externalities, positive or negative, generated by human activities. Sustainable economic development is characterized by maintaining a reasonable, long-term balance between economic development and environment integrity.